THE INFLUENCE OF THE HAPPY CARD MEDIA PJBL MODEL ON THE LEARNING OUTCOMES OF CLASS III CIVIC LEARNING SDN MASANGAN WETAN: PENGARUH MODEL PJBL BERBANTU MEDIA HAPPY CARD TERHADAP HASIL BELAJAR SISWA PEMBELAJARAN PKn KELAS III SDN MASANGAN WETAN - Dinda Pratiwi (Universitas Negeri Surabaya, 2023)
Civics learning in elementary school is expected to form students who are active, creative and help in thinking critically, analytically, behaving and acting democratically to run a life based on Pancasila and the 1945 Constitution. In explaining Civics learning material, teachers tend to use the lecture method so that students are less active in the learning process. This study aims to determine whether or not there is an effect of the Project Based Learning (PjBL) model assisted by happy card media on student learning outcomes in Civics learning class III SDN Masangan Wetan. This research is a quantitative experimental research with PreExperiment Design design and this research design used One-Group Pretest-Posttest Design. This study uses data collection methods in the form of tests. The results of research conducted with the t-test showed a significant value (sig) (2-tailed) of 0.000 <0.05. This shows that there is an influence from before and after being given treatment in the form of a Project Based Learning (PjBL) model assisted by happy card media on the learning outcomes of third grade Civics learning students at SDN Masangan Wetan.